Improving Purchasing Decisions at Richeese Factory Through Customer Engagement - Salmah Fitrianingsih; Parlagutan Silitonga (Journal of Finance and Business Digital, 2023)
Business development is currently increasing, especially the fast food restaurant culinary business. The purpose of this study was to improve purchasing decisions with perceived price and product quality through the mediating role of customer engagement at Richeese Factory. The population in this study are all those who buy Richeese Factory. The sampling technique used purposive sampling with 175 respondents. Methods of data collection using questionnaires distributed to respondents. The analysis used is path analysis with the help of SmartPLS 3.3. The research results show that price perceptions have no effect on purchasing decisions, but other results show that there is a significant effect.